DIAGNOSIS LABORATORIK ANEMIA DEFISIENSI BESI - Dina Sophia Margina; Sianny Herawati; I W P Sutirta Yasa (Universitas Udayana, 2014)
Iron deficiency anemia is a decreament of iron level in the body. Iron deficiency anemiais oftenly seen, especially in the tropical countries or the third world country thatassociated with social economic rate. Iron deficiency anemia happens in more than onethird world’s population. Iron deficiency anemia can be caused by chronic hemorrhage,low intake of iron, absorption disturbance, and increasement of demand. To diagnose irondeficiency anemia, laboratoric examination is needed. The treatment can be causaltreatment, iron supplementation and another additional treatment.